Penerapan Metode Problem-Solving untuk Meningkatkan Keaktifan dan Hasil Belajar di Madrasah Tsanawiyah Negeri 9 Boyolali - Kumaidi; Bisri, Moh (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The main objective of this research is to apply the problem-solving method to increase activity and learning outcomes for the jurisprudence knowledge aspect in Class VIII C MTs Negeri 9 Boyolali Semester I 2022/2023 Academic Year. This research is classroom action research to increase student activity and learning outcomes. The research results show that the learning process using the problem-solving method is as follows: Stage 1: There is a clear problem to be solved 2: Search for data or information, Stage 3: Determine a temporary answer, Stage 4: Test the correctness of the answer, Stage: 5 Conclude. The implementation from cycle I to cycle II has improved. This research shows that the activity of pre-cycle conditions, cycle I and cycle II has increased. In the initial conditions of cycle I and cycle II, the percentage of active students increased from 59.4% - to 87.5% - 93.8% so that this also affected learning outcomes that had not yet reached the KKM, which continued to decline from pre-cycle to cycle I (46, 9% - 18.7%) from cycle I to cycle II (18.7% to - 0%). This research shows that student learning outcomes have improved after taking action. The percentage of students who have experienced an increase from pre-cycle to cycle I (53.1% to 81.3%) from cycle I to cycle II (81.3 to 100%). The indicator of the success of CAR (Classroom Action Research) is that the CAR is said to be successful if the learning outcome score reaches 90%. The table shows that the percentage of students whose grades have been completed has reached 100%, so PTK has been successful.